CSR SPENDING AND COMPANY PERFORMANCE OF SELECT COMPANIES IN INDIA - Reddy, V.V.K.; Adavelli, S.R. (University of Jaffna, 2021)
The influence of Corporate Social Responsibility has found higher recognition by those who see social good as linked to a company’s long- term business decisions as well as those who see it as essential in its own right aligning with business ethics and corporate citizenship. This paper is to analyze the relationship among expenditure on social cost, total profits after tax, total assets, paid-up capital, and the total turnover of the 15 sample companies. It is found that the average amount spent by sample companies as a percentage of total profits after tax was 2.26% which is more than the minimum requirement (2.0%) of the companies Act 2013. t statistic of the total profits after tax, total assets, total turnover, and paid-up capital with p value (0.000 < 0.01) at a 1% level of significance indicates that reject the null hypothesis and concludes that regression coefficients are significant in estimating CSR spending.
Keywords: CSR spending; ROA; ROE; ROS; Company performance; Total profits after tax